HEMOLYSIN III SUPER FAMILY PROTEIN, A POTENTIAL VIRULENCE FACTOR IN ENTEROBACTER CLOACAE ASSOCIATED WITH MASS MORTALITY IN LABEO BATA ELICITS IMMUNE RESPONSE DURING INFECTION - ABDULLA, TANUJA; PARIA , P.; BERA, A. K.; MANNA, R. K.; THACHIL, MADONNA T.; DAS, B. K. (Journal of the Inland Fisheries Society of India, 2024)
Mass mortality due to hemorrhagic ulcerative lesions in Indian Minor Carp (Labeo bata) has been reported in the East Kolkata Wetland, Kolkata, West Bengal, India. Enterobacter cloacae as the etiological agent responsible for the infection in L. bata was characterised. The study identified the Haemolysin III superfamily protein in E.cloacae. The expression levels of immune-related genes Interleukin-10 (IL-10), Complement factor 3a (C3a), and Heat Shock Proteins 70 (Hsp70) were found to be up-regulated in the kidney’s and liver of experimentally challenged fish after 12h of post injection. This is the first report of L. bata infection by E. cloacae.